2015
DOI: 10.1111/vsu.12405
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Prognostic Factors for Canine Splenic Lymphoma Treated by Splenectomy (1995–2011)

Abstract: Based on our sample population, splenectomy alone was an effective treatment for splenic lymphoma in cases with disease confined to the spleen. Chemotherapy may not improve survival in cases of lymphoma restricted to the spleen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…These data corroborate the few studies from other countries, where the incidence of indolent lymphomas in the spleen was higher compared to high grade lymphomas (Van Stee et al 2015). A study of 28 cases of primary splenic lymphoma showed 71.4% of indolent tumors and marginal zone B-cell lymphoma was also the most prevalent (39.3% of cases), followed by mantle cell lymphoma (32.1%) (Van Stee et al 2015). Interestingly, although mantle cell lymphoma was the second most common in that study, no case of this type was seen in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These data corroborate the few studies from other countries, where the incidence of indolent lymphomas in the spleen was higher compared to high grade lymphomas (Van Stee et al 2015). A study of 28 cases of primary splenic lymphoma showed 71.4% of indolent tumors and marginal zone B-cell lymphoma was also the most prevalent (39.3% of cases), followed by mantle cell lymphoma (32.1%) (Van Stee et al 2015). Interestingly, although mantle cell lymphoma was the second most common in that study, no case of this type was seen in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Indolent splenic lymphomas were more prevalent (63.7%) in this study, of which 60.7% of the cases were diagnosed as marginal zone B-cell lymphoma. These data corroborate the few studies from other countries, where the incidence of indolent lymphomas in the spleen was higher compared to high grade lymphomas (Van Stee et al 2015). A study of 28 cases of primary splenic lymphoma showed 71.4% of indolent tumors and marginal zone B-cell lymphoma was also the most prevalent (39.3% of cases), followed by mantle cell lymphoma (32.1%) (Van Stee et al 2015).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The vast majority of cases lack detectable peripheral node infiltration and peripheral blood or bone marrow involvement appears to be very uncommon. Biologically, cMCL is reported to be an indolent disease and a series of nine dogs with splenic MC had a 1 year survival rate of 88.9% and an overall survival period of 502 days [113]. …”
Section: B-cell Neoplasmsmentioning
confidence: 99%